Upaya Peningkatan Kemampuan Membaca Al-Qur’an bagi Remaja dengan Metode Qiroati - Sunandar, Asep (Khidmat, 2021)
The teaching of reading and writing the Qur'an is one of the obligations that must be carried out or studied by every Muslim because it is one way to understand the Qur'an well, and it has to do with ritual worship such as prayer, pilgrimage and prayer. In learning to read or write the Qur'an, of course, you can't do it right away, but you have to go through stages. Therefore, in teaching reading and writing the Qur'an, a practical and fast method is also needed. The Qiroati method is one method that is directly without spelling and gets used to reading tartil according to the rules of recitation.